Boosting third-order nonlinearities in rutile TiO2 by chromium doping - Brinkmann, Marius; Meier, Falco; Spedt, Vladimir; Meier, Cedrik (Optics Express)
In this study, we investigate the impact of chromium-induced point defects on the nonlinear optical properties and electric-field-induced second harmonic generation (EFISH) in rutile titanium dioxide (TiO 2 ). Chromium thin films were deposited by electron beam evaporation on (001)-oriented bulk TiO 2 substrates and subsequently diffused into the lattice in a tube furnace under a nitrogen atmosphere at 900 °C. The introduction of chromium significantly enhanced the third harmonic generation (THG) of a 1560 nm laser, with an amplification factor of up to 8.3, indicative of an enhanced third-order nonlinear susceptibility, χ (3) . Moreover, the application of an external voltage induced a pronounced EFISH signal in the chromium-doped samples, further confirming the enhanced nonlinear response. These results demonstrate that defect engineering via chromium doping in rutile TiO 2 offers a promising pathway for the development of high-performance nonlinear optical devices.

What We Talk About When We Talk About K-12 Computing Education - Schulte, Carsten; Sentance, Sue; Sparmann, Sören; Altin, Rukiye; Friebroon-Yesharim, Mor; Landman, Martina; Rücker, Michael T.; Satavlekar, Spruha; Siegel, Angela; Tedre, Matti; Tubino, Laura; Vartiainen, Henriikka; et al. (2024 Working Group Reports on Innovation and Technology in Computer Science Education)

Surfacing Educational Traditions in European K–12 Computing Curricula: A Large-Scale NLP-Based Comparison - Sparmann, Sören; Altin, Rukiye; Mühling, Andreas; Schulte, Carsten (Proceedings of the 25th Koli Calling International Conference on Computing Education Research)

Rough Data in an Evolution System Generalizing 1D Thermoviscoelasticity with Temperature-Dependent Parameters - Winkler, Michael (Applied Mathematics & Optimization)

Special issue of Journal of Lie Theory dedicated to Karl-Hermann Neeb on the occasion of his 60th birthday (J. Lie Theory)

Modeling approaches for the decomposition behavior of preconsolidated rovings throughout local deformation processes - Gröger, Benjamin; Gerritzen, Johannes; Hornig, Andreas; Gude, Maik (Sheet Metal 2025)
This paper investigates two modeling approaches for the simulation of the deformation and decomposition behavior of preconsolidated rovings above the thermoplastic matrix{’} melting temperature. This is crucial for capturing the local material structure after processes introducing highly localized deformation such as mechanical joining processes between metal and fiber reinforced thermoplastics (FRTP). A generic finite element (FE) model is developed, incorporating interfaces discretized through either cohesive zone (CZ) elements or Coulomb friction-based contacts. The material parameters for the FE elements are derived from the initial stiffness of a statistical volume element (SVE) at micro scale modelled with an Arbitrary-Lagrange-Eulerian method for three load cases. The CZ properties calculated are based on the shear viscosity of the composite. The CZ and contact modelling approaches are evaluated using three load cases of the SVE, comparing force-displacement curves. Under simple loading conditions, such as normal pressure tension and bending, both methods produce similar results; however, in complex load cases, the CZ approach shows clear advantages in handling interface interactions and shows robust simulations. The CZ approach thus presents a promising method for simulating roving decomposition in FRTP-metal joining applications above the matrix{’} melting temperature.
Keywords: Finite Element Method (FEM); Process; Thermoplastic Fiber Reinforced Plastic

Efficient failure information propagation under complex stress states in fiber reinforced polymers: From micro- to meso-scale using machine learning - Gerritzen, Johannes; Hornig, Andreas; Gude, Maik (Sheet Metal 2025)
The failure behavior of fiber reinforced polymers (FRP) is strongly influenced by their microstructure, i.e. fiber arrangement or local fiber volume content. However, this information cannot be directly used for structural analyses, since it requires a discretization on micrometer level. Therefore, current failure theories do not directly account for such effects, but describe the behavior averaged over an entire specimen. This foundation in experimentally accessible loading conditions leads to purely theory based extension to more complex stress states without direct validation possibilities. This work aims at leveraging micro-scale simulations to obtain failure information under arbitrary loading conditions. The results are propagated to the meso-scale, enabling efficient structural analyses, by means of machine learning (ML). It is shown that the ML model is capable of correctly assessing previously unseen stress states and therefore poses an efficient tool of exploiting information from the micro-scale in larger simulations.
Keywords: Failure; Fiber Reinforced Plastic; Machine Learning

3D viscoelastic plastic model coupled with a continuum damage formulation for fiber reinforced polymers - Gerritzen, Johannes; Gröger, Benjamin; Zscheyge, Matthias; Hornig, Andreas; Gude, Maik (Materials & Design)

Manifold of mappings and regularity properties of half-Lie groups - Pinaud, Matthieu

Quality assurance of clinched joints using explainable machine learning - Gerritzen, Johannes; Chopra, Kunal; Reschke, Gregor; Hornig, Andreas; Brosius, Alexander; Gude, Maik (Journal of Advanced Joining Processes)

Modelling strategies for non-rotationally symmetric joints - Devulapally, Deekshith Reddy; Tröster, Thomas (Materials Research Proceedings)
Abstract. Accurate Finite Element Modeling (FEM) of joints is essential in the design of complex mechanical systems such as automotive body-in-white (BIW) structures, as it plays a critical role in evaluating their performance. Although well-established techniques exist for modeling rotationally symmetric joints, there remains a significant gap in effectively modeling non-rotationally symmetric joints. These joints are particularly relevant in the automotive BIW, where they can better accommodate anisotropic loading conditions. In this study, strategies for modeling non-rotationally symmetric joints were explored using finite element simulations in LS-DYNA. The findings demonstrate that discrete beam elements can capture the anisotropic characteristics of such joints. Two models were tested: a single-beam model for stiffness periodicity every 90°, and a three-beam model for stiffness periodicity every 120°. Force responses, stress distribution, and sheet bending behaviors were analyzed, confirming that discrete beam elements can accurately represent direction-dependent stiffness. These results establish a foundation for developing advanced joint modeling strategies in complex mechanical systems.

Intrinsic Motivation in Stem Outreach: An Analysis of External Factors in Voluntary and School-Based Lab Settings - Reckmann, Eileen; Temmen, Katrin (EDULEARN Proceedings)

Introduction of electronic lab notebooks in engineering education - opportunities for a cultural change - Müller, Laura; Meihöfener, Niclas; Siemoneit, Johannes Gabriel; Mozgova, Iryna (Engineering Education for Sustainable Development (EESD2025))

SMEs within a Data-Driven Sustainable Finance Framework: A European Survey - Rossmann, Felix; Greitens, Jan; Knoll, Lisa

Technik im Fokus: Eine qualitative Analyse kindlicher Themenwünsche in der non-formalen MINT-Bildung - Reckmann, Eileen; Temmen, Katrin

Multilevel fault diagnostics for railway applications using limited historical data - Aimiyekagbon, Osarenren Kennedy; Löwen, Alexander; Hanselle, Raphael; Rief, Thomas; Beck, Maximilian; Sextro, Walter (PHM Society Asia-Pacific Conference)
This study proposes a fault diagnostics methodology that addresses the challenges posed by highly imbalanced datasets typical of railway applications, where faulty conditions constitute the minority class. Fault diagnostics is performed from the component level upward, considering each sensor’s proximity to its respective critical component. Advanced signal analysis, feature engineering, and automated data-driven model generation techniques were explored to achieve comprehensive diagnostics, such that the model development process accounts for variations in the operating conditions and differing levels of information availability. The proposed methodology is evaluated on datasets from the MONOCAB, for scenarios with limited faulty instances and on the Beijing 2024 IEEE PHM Conference data challenge, which focused on fault diagnostics of railway systems under various fault modes and operating conditions.
Keywords: MONOCAB; Beijing Data Challenge; Diagnostics of railway systems

"Wofür bin ich denn hier, wenn ich nicht in irgendeiner Weise auch helfen kann?" Zur Rolle der Lehrkraft beim selbstständigen Songwriting im Unterricht - Godau, Marc; Barreiro, Julia; Hermann, Katharina; Neuhausen, Timo; Maxelon, Dominik; Weidner, Verena (46. Jahresband des Arbeitskreises Musikpädagogische Forschung/46th Yearbook of the German Association for Research in Music Education)
The article explores the role of teachers in self-directed songwriting in school music based on the informal learning approach. It investigates a didactic design that was implemented in six schools and was empirically researched utilizing si-tuational analysis. Based on tensions, that emerge due to conflicting expectations, it can be shown, that the teacher's role extends beyond the dichotomy of directive instruction versus open facilitation. Instead, it encompasses an interplay of six divergent roles which are discussed in their positions in relation to each other. These considerations enrich the understanding of teaching practices in popular music education, emphasizing the redefinition of teacher-student relationships for song-writing in school music.

Die Rolle institutionalisierter Standards für die Hybridisierung musikalischer Praxen. Zur Soziomaterialität von Songwriting-Producing im Bedroom-Studio - Neuhausen, Timo (46. Jahresband des Arbeitskreises Musikpädagogische Forschung/46th Yearbook of the German Association for Research in Music Education)
The role of institutionalized standards for the hybridization of musical practices. On the socio-materiality of songwriting-producing in the bedroom studio This study examines the socio-materiality of hybrid music practices in bedroom studios, focusing on the interplay between traditional music education institutions and YouTube education. A single case situational analysis reveals how standardized instrumental and music production practices are combined to form a hybrid practice. It shows that traditional music education institutions, such as music schools and conservatories, specialize in the selection of chord tones, while You-Tube videos focus on sound design. Using an actor-network theory approach, the study demonstrates the permeability of informal and institutional learning spaces. The findings suggest that songwriting-producing is not simply a sum of different practices, but rather a process of negotiation and compromise between different standards and goals, as well as the distribution of practice between humans and technology.

Über Rätsel zur Quantenphysik – Eine spielerische Heranführung an ein abstraktes Thema - Ebert, Marc; Temmen, Katrin

Bolted Langevin transducers with leadfree piezoelectric ceramics - Scheidemann, Claus; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias
Lead-containing piezoelectric ceramics are still the base for today’s ultrasonic transducers used in broad applications. This is partly due to missing powerful lead-free piezoelectric ceramic parts in the commercial market. There has been much research on lead-free materials but developing them into marketable parts seems to be an ongoing process. The actual exemption of ROHS has expired, but as the new exemption has already been requested, ceramic suppliers keep on selling lead containing products. Nevertheless, these should be replaced by lead-free alternatives for environmental and health issues. This contribution focuses on exploring the technological readiness level of lead-free hard piezoceramics for prestressed ultrasonic transducers. A small series of bolted Langevin transducers was set up with standard PZT material and three commercial lead-free variants. Results of the building process from individual ring ceramic characteristics to transducer load tests are presented. The main finding of this study is that the lead-free materials technically can compete with the standard PZT for medium-power applications. Some adaptations in the ultrasonic system must be done: the geometry must be altered to fit resonance frequency, and higher voltages or thinner ceramics are needed to achieve the same vibration level at low load. For reaching same power, the volume of lead-free ceramics must be 1.5 to 3 times larger. As already promoted in literature, mechanical losses at high vibration levels are smaller for the lead-free materials. This might help to argument lead-free piezoelectric materials in some applications. References 1. Directive 2011/65/EU of the European Parliament and of the Council of 8 June 2011 on the Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment. EUR-Lex Document 02011L0065-20240801. Available online: http://data.europa.eu/eli/dir/2011/65/2024-08-01 (accessed on 24 January 2025). 2. Langevin, P. (1918) Method and Apparatus for Transmitting and Receiving Submarine Elastic Waves Using the Piezoelectric Properties of Quartz. French Patent Office; Patent No. FR505703. 3. Hemsel, T.; Twiefel, J. (2023) Piezoelectric Ultrasonic Power Transducers. In Encyclopedia of Materials: Electronics; Academic Press: Oxford, UK; pp. 276–285. https://doi.org/10.1016/b978-0-12-819728-8.00047-4. 4. ATHENA Technologie Beratung GmbH (2025) Description of Ultrasound Generator. Available online: http://shop.myathena.de/epages/12074748.sf/de_DE/?ObjectPath=/Shops/12074748/Products/AM200 (accessed on 13 January 2025). 5. Littmann, W.; Hemsel, T.; Kauczor, C.; Wallaschek, J.; Sinha, W. (2003) Load-adaptive phase-controller for resonant driven piezoelectric devices. Proc. World Congr. Ultrason. 2003, 48, 547–550. 6. Scheidemann, C., Bornmann, P., Littmann, W., & Hemsel, T. (2025). Lead-Free Ceramics in Prestressed Ultrasonic Transducers. Actuators, 14(2), 55. https://doi.org/10.3390/act14020055
Keywords: lead free piezoelectric ceramics; bolted Langevin transducer; medium power ultrasound.